A FORMAÇÃO DE PROFESSORES PARA A EDUCAÇÃO ESPECIAL - Gonzaga da Silva, Maristela (Universidade Federal do Tocantins, 2021)
The present work is about the Formation of Teachers for the Special Education, more specifically, I bring the historical context of the Special Education and the Formation of Teachers in this área. In order to have a better understanding of the present, it is necessary to resort to the past in order to draw a timeline to understand the evolution of phenomena. I come to approach history from Antiquity to the present day, showing its development through historical periods. And in the discourse, the objective is to address the importance of Teacher Education. The choice of this theme is due to the observation, during my studies, of the insufficient training of teachers who work with children with disabilities in schools in the North region. This monograph highlights the importance of specialized training in Special Education, and to analyze how teachers work in Regular Education and in the Resource Room.